Proximate Compositions and Biological Activities of Caulerpa lentillifera - Risa Nofiani; Sigit Hertanto; Titin Anita Zaharah; Sutarman Gafur (Molekul, 2018)
Caulerpa lentillifera is an edible and functional seaweed due to its high nutritional compositions and its biological activities.  In this study, C. lentillifera was evaluated for its proximate compositions (moisture, ash, protein, lipid and fiber contents) and its biological activities (antimicrobial, anti-oxidant, and toxicity). Moisture content, crude lipid, crude protein, and crude fiber were determined using oven method, soxhlet extraction, semi-micro Kjeldhal, and hydrolysis, respectively.  Fresh C. lentillifera of Natuna Island, Indonesia, showed its higher level content of ash, crude lipid, and crude fiber compared to that of fresh C. lentillifera of Penghu, Taiwan.  For its biological activity assays, the extracts were prepared from fresh and dry C. lentillifera (FC and DC).  Both of the extracts showed the broad spectrum of weak antimicrobial using well-diffusion agar tests and antioxidant activities using a modified linoleic acid emulsion system.  The toxicity for both extracts was determined using brine shrimp lethality test.  DC extract showed its very low toxicity level and there was no toxicity for FC.  Hemolytic activity was determined using red blood assay.  Both extracts showed their low hemolytic activities (about 5-13%) for the concentration of 100 and 150 μg/mL, but the activity increased sharply (about 96%) on the concentration of 200 μg/mL.  It was concluded that C. lentillifera has a potency as a functional food due to containing secondary metabolites with various biological activities.